Insight into Metabolic 1H-MRS Changes in Natalizumab Induced Progressive Multifocal Leukoencephalopathy Brain Lesions - Schneider, Ruth; Bellenberg, Barbara; Hoepner, Robert; Ellrichmann, Gisa; Gold, Ralf; Lukas, Carsten (Frontiers in Neurology, 2017)
Background Progressive multifocal leukoencephalopathy (PML) is a severe complication of immunosuppressive therapies, especially of natalizumab in relapsing–remitting multiple sclerosis (MS). Metabolic changes within PML lesions have not yet been described in natalizumab-associated PML in MS patients. Objective To study metabolic profiles in natalizumab-associated PML lesions of MS patients by 1H magnetic resonance spectroscopy (1H-MRS) at different stages during the PML course. To assess changes associated with the occurrence of the immune reconstitution inflammatory syndrome (IRIS). Methods 20 patients received 1H-MRS and imaging at 3 T either in the pre-IRIS, IRIS, early-post-PML, or late post-PML setting. Five of these patients received individual follow-up examinations, including the pre-IRIS or IRIS phase. Clinical worsening was described by changes in the Karnofsky Performance Scale (KPS) and the expanded disability status scale (EDSS) 1 year before PML and scoring at the time of 1H-MRS. Results In PML lesions, increased levels of the Lip/Cr ratio, driven by rising of lipid and reduction of Creatine, were found before the occurrence of IRIS (p = 0.014) with a maximum in the PML–IRIS group (p = 0.004). By contrast, marked rises of Cho/Cr in PML lesions were detected exclusively during the IRIS phase (p = 0.003). The Lip/Cr ratio decreased to above-normal levels in early-post-PML (p = 0.007, compared to normal appearing white matter (NAWM)) and to normal levels in the late-post-PML group. NAA/Cho was reduced compared to NAWM in the pre-IRIS, IRIS, and early-post-PML group. In NAA/Cr, the same effect was seen in the pre-IRIS and early-post-PML group. These cross-sectional results were confirmed by the individual follow-up examinations of four patients. NAA/Cho, Cho/Cr, and the lipid rise relative to NAWM in PML lesions were significantly correlated with the residual clinical worsening (KPS change) in post-PML patients (Spearman correlations ρ = 0.481, p = 0.018; ρ = −0.505, p = 0.014; and ρ = −0.488, p = 0.020). Conclusion 1H-MRS detected clinically significant dynamic changes of metabolic patterns in PML lesions during the course of natalizumab-associated PML in MS patients. Lip/Cr and Cho/Cr may provide additional information for detecting the onset of the IRIS phase in the course of the PML disease.